Gut Prevotellaceae-GABAergic septohippocampal pathway mediates spatial memory impairment in high-fat diet-fed ovariectomized mice - Shuai Zhang; Lu Zeng; Jing Ma; Wentao Xu; Yang Qu; Xuqiao Wang; Xiaobin An; Qin Wang; Yan Wu; Dongyang Wang; Haihui Chen; Jing Ai (Neurobiology of Disease, 2023)
Clarifying the risk factors and mechanisms that contribute to the onset of cognitive impairment following estrogen depletion is essential for improving the quality of life of older females. In the current study, using behavioral tests, 16S rDNA sequencing, in vivo and in vitro electrophysiology, optogenetics and chemogenetics, we found that high-fat diet (HFD)-accelerated impairment of hippocampus-dependent memory, gut microbiota, and hippocampal theta rhythmogenesis in ovariectomized (OVX) mice and fecal microbiota transplantation rescued these phenomena. The identification of fasting-activated medial septal neurons showed that PV+ GABAergic neurons in the medial septal area (MSA) respond to gut sensory signals. Optogenetic activation of septohippocampal PV+ GABAergic fibers (but not cholinergic fibers) significantly rescued hippocampal theta rhythmogenesis and spatial memory in HFD-fed OVX mice. Resistant starch supplementation (RSHFD) rectified the gut Prevotellaceae and considerably alleviated reduced septal gut-responsive neurons, decreased hippocampal theta rhythm, and impaired hippocampus-dependent memory in HFD-fed OVX mice. Furthermore, chemogenetic inhibition of septal PV+ GABAergic neurons reversed the neuroprotective effects of resistant starch supplementation. These findings highlight the notable gut-sensory nature of medial septal PV+ GABAergic neurons. A HFD accelerates estrogen deficiency-induced cognitive impairment by disrupting the gut Prevotellaceae-septo-hippocampal pathway. This study contributes to a better understanding of the precise gut-brain control of cognition and cognitive impairment in postmenopausal females.